Adrenergic Autoantibody‐Induced Postural Tachycardia Syndrome in Rabbits. Issue 19 (1st October 2019) - Li, Hongliang; Zhang, Gege; Zhou, Liping; Nuss, Zachary; Beel, Marci; Hines, Brendon; Murphy, Taylor; Liles, Jonathan; Zhang, Ling; Kem, David C.; Yu, Xichun
Abstract : Background: Previous studies have demonstrated that functional autoantibodies to adrenergic receptors may be involved in the pathogenesis of postural tachycardia syndrome. The objective of this study was to examine the impact of these autoantibodies on cardiovascular responses to postural changes and adrenergic orthosteric ligand infusions in immunized rabbits. Methods and Results: Eight New Zealand white rabbits were coimmunized with peptides from the α1‐adrenergic receptor and β1‐adrenergic receptor (β1AR). Tilt test and separate adrenergic agonist infusion studies were performed on conscious animals before and after immunization and subsequent treatment with epitope‐mimetic peptide inhibitors. At 6 weeks after immunization, there was a greater percent increase in heart rate upon tilting compared with preimmune baseline. No significant difference in blood pressure response to tilting was observed. The heart rate response to infusion of the β‐adrenoceptor agonist isoproterenol was significantly enhanced in immunized animals, suggesting a positive allosteric effect of β1AR antibodies. In contrast, the blood pressure response to infusion of the α1‐adrenergic receptor agonist phenylephrine was attenuated in immunized animals, indicating a negative allosteric effect of α1‐adrenergic receptor antibodies. Injections of antibody‐neutralizing peptides suppressed the postural tachycardia and reversed the altered heart rate and blood pressure responses to orthosteric ligand infusions in immunized animals at 6 and 30 weeks. Antibody production and suppression were confirmed with in vitro bioassays. Conclusions: The differential allosteric effect of α1‐adrenergic receptor and β1AR autoantibodies would lead to a hyperadrenergic state and overstimulation of cardiac β1AR. These data support evidence for an autoimmune basis for postural tachycardia syndrome. Abstract : See Editorial Miller and Doherty